Anterior distal femoral hemiepiphysiodesis in children with cerebral palsy: Establishing surgical indications and techniques using the modified Delphi method and literature review. (February 2022) - Shore, Benjamin J; McCarthy, James; Shrader, M Wade; Graham, H Kerr; Veerkamp, Matthew; Rutz, Erich; Chambers, Henry; Davids, Jon R; Narayanan, Unni; Novacheck, Tom F; Pierz, Kristan; Dreher, Thomas; et al.
Purpose: The purpose of this study was to develop consensus for the surgical indications of anterior distal femur hemiepiphysiodesis in children with cerebral palsy using expert surgeon opinion through a modified Delphi technique. Methods: The panel used a 5-level Likert-type scale to record agreement or disagreement with 27 statements regarding anterior distal femur hemiepiphysiodesis. Consensus was defined as at least 80% of responses being in the highest or lowest 2 of the Likert-type ratings. General agreement was defined as 60%–79% falling into the highest or lowest 2 ratings. Results: For anterior distal femur hemiepiphysiodesis, 27 statements were surveyed: consensus or general agreement among the panelists was achieved for 22 of 27 statements (22/27, 82%) and 5 statements had no agreement (5/27, 18%). There was general consensus that anterior distal femur hemiepiphysiodesis is indicated for ambulatory children with cerebral palsy, with at least 2 years growth remaining, and smaller (<30 degrees) knee flexion contractures and for minimally ambulatory children to aid in standing/transfers. Consensus was achieved regarding the importance of close radiographic follow-up after screw insertion to identify or prevent secondary deformity. There was general agreement that percutaneous screws are preferred over anterior plates due to the pain and irritation associated with plates. Finally, it was agreed that anterior distal femur hemiepiphysiodesis was not indicated in the absence of a knee flexion contracture. Conclusion: Anterior distal femur hemiepiphysiodesis can be used to treat fixed knee flexion contractures in the setting of crouch gait, but other associated lever arm dysfunctions must be addressed by single-event multilevel surgery. Level of evidence: V